Importance-Performance Analysis in Public Transport Level of Service: A Case Study of The Trans Koetaradja Bus in Banda Aceh - Mutiawati, Cut; Suryani*, Fitrika Mita; Anggraini, Renni; Isya, Muhammad (Aceh International Journal of Science and Technology, 2022)
Traffic congestion often occurs in many cities, particularly in developing countries, mainly due to excessive private vehicles instead of public transport. To solve the problem, public transport should improve its level of services to attract more people to use it. Therefore, it is essential to observe to what extent people's satisfaction with public transport regarding its operation. This research aims to analyze the satisfaction level of bus passengers in Banda Aceh City concerning the expected satisfaction and observed performance. The passengers' satisfaction level was analyzed using the important performance analysis (quadrant analysis) method. The results showed that people's perception of the level of service of Trans Koetaradja buses was still acceptable. However, the arrival and departure time still needs to be improved. Further, dedicated bus lane planning is essential to avoid traffic jams so that the travel time can be much shorter. The fleet of operating buses is sufficient, and free-of-charge fares still need to be applied.